أهمية التخدير الموضعي في التحري المباشر عن الليشمانيا الجلدية: دراسة مخبرية - عساف، أمال (جامعة البعث, 2017)
Cutaneous leishmaniasis is an old endemic disease in Syria. And incidence of the disease is on a rise during the crisis, because of suitable ecological circumstances for phlebotomes and migration of people etc..,. At present, novel diagnostic methods including polymerase chain reaction technique PCR are in use, but still limited to reference or research laboratories in Syria, so direct microscopic examination of lesion scrapings still continues to be the diagnostic method most widely applied because of speed, low cost, and ease of performance of this technique. We performed this study aimed to compare the sensitivity of parasite detection by microscopic examination in samples collected by conventional technique and samples collected after local anesthetic with lidocaine and adrenaline of the same lesions in patients with suspected leishmaniasis. 104 patients clinically diagnostic with cutaneous leishmaniasis were included in this study, they attended the outpatient clinics of the dermatology and venereal diseases hospital in Damascus. The following diagnostic techniques were carried out for diagnosis of cutaneous leishmaniasis including: dermal scraping from lesions before and after local anesthetic with lidocaine and adrenaline, then we analyzed the results of two different technique in direct microscopic examination of parasite detection. Our results indicated that the sensitivity of the dermal scraping increases when lidocaine and adrenaline are used. And samples taken after local anesthetic of the lesion allow parasitologic confirmation with higher sensitivity 73.08% than the routinely used technique 60.58%, P=0.004 and the difference is still significant when lesions are less than 3 months 83.82 % vs 69.12 % P=0.013. The present study concluded that technique used local anesthetic with lidocaine and adrenaline is more sensitive for diagnosis of cutaneous leishmaniasis than conventional one, so we recommend using of local anesthetic of lesions especially for lesions last less than 3 months when routinely used technique is negative.
الليشمانيا الجلدية من الأمراض القديمة المستوطنة في سوريا ومعدل الوقوع السنوي في ارتفاع في ظل الأزمة بسبب توفر الشروط البيئية الملائمة لحياة الفواصد وهجرة السكان وغيرها. في الوقت الحالي طرق تشخيصية حديثة منها التفاعل التسلسلي للبولميراز PCR وضعت في الاستخدام، ولكن مازالت حكرا على المخابر المرجعية والبحثية في سوريا، ومايزال الفحص المجهري المباشر عن الطفيلي في الكشاطات الجلدية الطريقة الأكثر انتشار يعود ذلك إلى سرعتها وانخفاض كلفتها وسهولة تطبيقها . أجرينا هذا البحث بهدف المقارنة بين حساسية التحري المباشر عن الطفيلي في كشاطات جلدية محضرة بالطريقة التقليدية وكشاطات جلدية من نفس الآفات بعد التخدير الموضعي بالليدوكائين والأدرينالين عند المرضى المشكوك بإصابتهم بالليشمانيا الجلدية. شملت الدراسة 104 مريض شخص لديهم ليشمانيا جلدية سريريا من مراجعي العيادات الخارجية في مشفى الأمراض الجلدية والزهرية الجامعي بدمشق. أجرينا لتشخيص الليشمانيا الجلدية طريقتين: كشاطات جلدية قبل وبعد التخدير الموضعي بحقن الليدوكائين والأدرينالين لنقس الآفات ثم قمنا بتحليل نتائج الطريقتين المختلفتين في الفحص المجهري المباشر للتحري عن الطفيلي. أشارت نتائجنا إلى أن حساسية الكشاطة الجلدية تزداد عند استخدام الليدوكائين والأدرينالين وأن العينات بعد التخدير الموضعي ذات حساسية أعلى 73.08% من تلك المحضرة بالطريقة التقليدية P=0.004, 60.58% وبقي الفرق ذو مغزى إحصائي في الآفات الحديثة بعمر أقل من 3 أشهر 83.82% مقابل P=0.013- 69.12% نستنتج من الدراسة الحالية بأن حساسية التحري المباشر باستخدام التخدير الموضعي بالليدوكائين والأدرينالين أعلى منها بالطريقة التقليدية لذلك نوصي بالتخدير الموضعي للآفات خاصة التي أعمارها أقل من 3 أشهر عند كون التحري بالطريقة التقليدية سلبيا.
Keywords: الأمراض الجلدية -- داء الليشمانيات -- التخدير الموضعي -- الفحص المباشر -- المجتمع السوري